Evolving role of clinical pharmacists in assessment of clinical and modern health care services - Unnissa, Zeenath; Mudassir, Mohammed; Ali, Syed Eshaan; Hussain, Muznah Muzaffar (International Journal of Basic & Clinical Pharmacology, 2025)
Clinical pharmacy is a pharmacy profession in which clinical pharmacists as health care professionals helps and provide direct patient care with the medications. Clinical pharmacists work in many settings, including hospitals, clinics, long-term care facilities, and community pharmacies. Clinical pharmacists work directly with patients in a variety of ways. They utilise their understanding of pharmaceuticals (including dose, drug interactions, side effects, cost-effectiveness, and so on) to assess if a medication plan is appropriate for their patients. Patient education and counselling on effective pharmaceutical usage are critical components of pharmacists' increasingly important duties. Pharmacists can detect and address any drug-related issues during counselling, as well as offer information that enhances patients' treatment compliance and raises the standard of care. Pharmacists have a critical role in detecting, identifying, preventing, and managing adverse drug reactions. Pharmacists play a crucial role in reporting adverse drug reactions (ADRs), which can lead to product withdrawal or label modifications. Clinical pharmacist can improve medication review, identify drug-related issues, provide treatment suggestions, and promote medication compliance. Pharmacists can also help enhance drug safety by working with other healthcare providers to create patient-centered medication management regimens. In this position, chemists can analyse prescription histories, identify potential drug-related issues, and provide recommendations to optimise medication management.